Comparative Effects of Three Iron Chelation Therapies on the Quality of Life of Greek Patients with Homozygous Transfusion-Dependent Beta-Thalassemia. (17th December 2012) - Goulas, Vasilis; Kourakli-Symeonidis, Alexandra; Camoutsis, Charalambos
Abstract : This prospective study assessed the quality of life of patients with homozygous transfusion-dependent beta-thalassemia in Greece receiving three different iron chelation treatments. Patients enrolled were receiving one of the following chelation therapies: deferoxamine (n = 21 ), deferasirox (n = 75 ), or deferoxamine in combination with deferiprone (n = 39 ). The three groups were compared in terms of their quality of life, satisfaction and adherence to treatment, control of their health, and self-esteem through the completion of five questionnaires. A higher percentage of patients receiving deferoxamine felt that their treatment negatively influenced their body and skin appearance and limited their ability to work, attend school, and perform daily tasks (P = 0.0066 ). The adherence to treatment rate and self-esteem were the lowest in the deferoxamine group (P < 0.05 ). The deferoxamine group also had the lowest physical component summary score in the SF-36 questionnaire (P = 0.014 ). This study suggests that the quality of life of beta-thalassemia patients receiving chelation therapy is dependent on the type of iron chelation treatment they receive. The study provides insight into important factors associated with the quality of life of these patients, which are essential for developing a more suitable clinical support team and counseling in order to maximize the treatment benefits for these patients in daily clinical practice.